Isozyme variation between two closely related species Crangon crangon (L.) and Crangon allmanni kinahan (decapoda, caridea) - Abdullah, Rosmann; Ab Shukor, Nor Aini (Brill Academic Publishers, 1993)
Crangon crangon (L.) and C. allmanni Kinahan were screened at 11 enzyme loci for electrophoretically detectable variation. The mean observed heterozygosity was 0.1346 + 0.06295 in C. crangon and 0.0567 + 0.0352 in C. allmanni. The possible causes of these rather low levels of genetic variation are considered in relation to the physical factors and feeding behaviour. The results also suggest that C. crangon and C. allmanni are two separate species that differ genetically although morphologically similar.